Comparison of metabolism, gut histology, and microbiota between Schizothorax lissolabiatus and Schizothorax griseus under identical farming conditions - Zhong, Chuanyan; Chen, Li; Huang, Zhengwei; Hu, Yuan; Jiang, Yujie; Zhou, Jun; Long, Xiaowen (Frontiers in Marine Science, 2024)
Schizothorax lissolabiatus and Schizothorax griseus are native Chinese fish species with significant ecological and economic importance. We wanted to support sustainable aquaculture practices by exploring the differences in metabolic, histological, and microbiota between the two Schizothorax species. This study analyzed and compared the digestive enzyme activities, metabolic indicators, gut histology, and microbiota composition of S. lissolabiatus and S. griseus under identical farming conditions. Our comparative analysis reveals both shared characteristics and species-specific differences. While a-amylase and trypsin activities showed no significant differences between species, a consistent trend was observed, with enzyme activity highest in the hindgut, followed by the midgut, foregut, esophagus, and liver. In terms of specific metabolic markers, S. griseus shows higher lipase activity in the liver and foregut, as well as higher aspartate aminotransferase and catalase levels in the liver, along with an increased serum glucose content compared to S. lissolabiatus. Serum metabolomics analysis revealed 21 differentially abundant metabolites linked to glycerophospholipid metabolism, autophagy, purine metabolism, and necroptosis, reflecting distinct metabolic adaptations and nutritional needs for each species. These metabolic differences provide a basis for optimizing feed composition and aquaculture practices tailored to each species. Notably, S. lissolabiatus displays a significantly higher goblet cell count in the hindgut compared to S. griseus. Additionally, both species exhibit greater villi number, length, width, crypt depth, and muscle thickness in the esophagus than in the foregut, midgut, and hindgut. S. griseus also has a higher number of operational taxonomic units (OTUs) and greater microbial diversity in its intestinal microbiota, which may enhance its nutrient utilization capabilities. While both species’ dominant microbial phyla include Fusobacteria, Firmicutes, Proteobacteria, and Bacteroidetes, S. griseus demonstrated superior lipid digestion capabilities. Furthermore, the midgut and hindgut in both species display higher starch and protein digestive enzyme activities than other digestive tissues. These findings highlight the physiological differences between the two Schizothorax species, suggesting targeted strategies to improve health, growth, and sustainability in aquaculture.